The Role of KKM 43 Untirta Students in Improving the Quality of Sukamanah Village, Rajeg District, Tangerang Regency Based on Health, Education, Social and Religion - Maria, Vera; KKM 43 Tematik UNTIRTA 2024 (PT FORMOSA CENDEKIA GLOBAL, 2024)
Student Work Lectures (KKM) are one of the outdoor activities carried out by students with the aim of providing services to the community and helping them in solving development problems. Through KKM, students serve the community in various aspects of development, including: (1) outdoor activities, (2) implementation in community areas such as villages, (3) community services as the main focus, and (4) helping the community in overcoming challenges development in the village. The implementation of KKM by Group 43 is located in Sukamanah Village, Rajeg Regency, Tangerang City. Sukamanah Village is one of the developed villages in Tangerang Regency but also needs more attention to improving the welfare of rural communities. Sukamanah Village consists of 11 sub-districts, and its residents mainly work as daily workers, personal businesses and livestock. Apart from that, the majority religion in this village is Islam.